2010
DOI: 10.1136/bjo.2010.185272
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of trabeculectomy with mitomycin C in patients with advanced glaucoma

Abstract: Background/Aims

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…They also found blebitis (n ¼ 8), bleb leak (n ¼ 15), and hypotony (n ¼ 4) in their study cases. 23 In our study, there were no cases of bleb leak, choroidal detachment, blebitis, or endophthalmitis, although these 16,24 In our series, 490% blebs were diffuse and mildly elevated with normal vascularity. There were no cases of avascular blebs in any study group.…”
Section: Discussionmentioning
confidence: 75%
“…They also found blebitis (n ¼ 8), bleb leak (n ¼ 15), and hypotony (n ¼ 4) in their study cases. 23 In our study, there were no cases of bleb leak, choroidal detachment, blebitis, or endophthalmitis, although these 16,24 In our series, 490% blebs were diffuse and mildly elevated with normal vascularity. There were no cases of avascular blebs in any study group.…”
Section: Discussionmentioning
confidence: 75%
“…Histopathologic studies revealed greater vascular occlusion with TCP than ECP, which may account for the significant complications such as hypotony and phthisis secondary to the chronic vascular occlusion seen with TCP. 13 They postulated that perfusion after ECP may explain the difference in efficacy and complication rates compared with TCP. Most patients in our study were controlled with additional topical medications, and only 1/73 (1.4%) was considered a candidate for additional glaucoma surgery to control IOP.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with advanced glaucoma four‐fifths of responders routinely performed trabeculectomy as the primary intervention. This may reflect recognition of successful outcomes and low IOP potentially achieved by augmented trabeculectomy, particularly in cases of advanced glaucoma . However, trabeculectomy is not universally considered for all advanced glaucoma patients as two‐thirds of responders sometimes considered performing GDI surgery for such patients.…”
Section: Discussionmentioning
confidence: 99%